A cost analysis of remote monitoring in a heart failure program. Issue 3 (1st October 2016) - Williams, Cynthia; Wan, Thomas T. H.
ABSTRACT: In this study, we examine the cost per outcomes of remote monitoring services in home health care. The methodology followed case matched design via retrospective chart reviews. Results of the chi-square test suggest that there were no significant associations between the intervention and hospital readmissions, χ 2  = (1, n  = 210, p -value = .71, phi = .71). An independent t -test compared group means of the number of skilled nursing visits and agency costs, p -value of .002 and .000, respectively, favoring the standard of care group. Based on this data set, the home care agency lost $153.46 for each hospital readmission in the intervention group. The cost of care complicated the agency's resources through an increase in nursing visits without offsetting the agency's investment into technology; the cost did not support remote monitoring as a financially viable option to the standard of care.